Pembangunan Sistem Pengelolaan Bank Soal Ujian Pilihan Ganda Secara Online - Silvia Ajrini; Tri Astoto Kurniawan; Denny Sagita Rusdianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Abstract Multiple choice test in Faculty of Computer Science, Brawijaya University has been constructed manually. Such construction encounters some problems, e.g. similarity in some questions created by some lecturers. In addition, lectures often forget to save every question that they ever made. All of these problems can be solved by an online questions bank management system for the multiple choice test. This system is expected to assist lecturers in creating and storing the questions safely as well as to detect the similarities among the questions. This system will be made in web, such as lectures can access anywhere and anytime. The system has been successfully tested using white box technique for unit and integration testings, and black box technique for validation testing. Keywords: online questions bank management system, multiple choice test, object oriented, waterfall model